2007
DOI: 10.5713/ajas.2007.1402
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Behavior of Pregnant Dairy Heifers during Last Trimester under Loose Housing System

Abstract: Thirty pregnant heifers (Jersey, Holstein Friesian and Hariana) were divided into three groups (10 animals/group) according to their stage of pregnancy viz. seven-month (181-210 days) pregnancy (SMP), eight-month (211-240 days) pregnancy (EMP) and nine-month (241-280 days) pregnancy (NMP) group. Time spent in various feeding activities (eating fodder, eating concentrate, standing rumination, sitting rumination and drinking) by each animal in the three pregnant groups was recorded in four different sessions (ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The shortened eating time ten days before calving was in agreement with previous reports [ 8 , 11 ]; in the latter study, cows spent 35% less time at the feed alley starting as early as 2 weeks prepartum [ 11 ]. Cows approaching parturition eat more slowly than nonpregnant cows [ 13 , 14 ], and combined with a shortened duration of eating, this is likely to reduce the overall feed intake. In the present study, eating time reached a minimum of 114 min on the day of calving but increased thereafter, and four days later, was in the reference interval of the control cows and the intervals established by other authors [ 5 , 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shortened eating time ten days before calving was in agreement with previous reports [ 8 , 11 ]; in the latter study, cows spent 35% less time at the feed alley starting as early as 2 weeks prepartum [ 11 ]. Cows approaching parturition eat more slowly than nonpregnant cows [ 13 , 14 ], and combined with a shortened duration of eating, this is likely to reduce the overall feed intake. In the present study, eating time reached a minimum of 114 min on the day of calving but increased thereafter, and four days later, was in the reference interval of the control cows and the intervals established by other authors [ 5 , 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pregnant cows ate less hay and considerably more slowly than the non-pregnant cows, and the duration of eating and rumination was therefore longer in the pregnant cows. Another study determined that rumination decreased significantly as pregnancy progressed; rumination lasted 450 minutes per day in the 7th and 8th months of pregnancy, but decreased to 429 minutes per day in the 9th month [ 14 ]. Monitoring cows during the transition period using the Hi-Tag electronic rumination monitoring system revealed that rumination was shortest at the time of parturition [ 15 ].…”
Section: Introductionmentioning
confidence: 99%